The relationship between information technology flexibility, capability and strategic alignment - Saeid Jorfi, 1971-, author; Khalil Md. Nor, supervisor; Fakulti Pengurusan (2014)
Thesis (Ph.D (Pengurusan)) - Universiti Teknologi Malaysia, 2014